Dialogue and description - Rubin, Bruce Joel; Solomon, Ed; Stevens, Dana; The Writers Guild Foundation; First Light Video Publishing; TMW Media Group, Inc. ([California] : The Writer Guild Foundation : TMW Media Group, Inc. (distributor))
This program teaches text and subtext, conveying emotion of the character and the situation they're in, research, rewriting dialogue, character profiling and specificity of vision
Title from title screen
Tape 3: Dialogue and description
Photography, Andrea Cimini
Keywords: Motion picture authorship; Creative writing